2010
DOI: 10.1055/s-0030-1268008
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Exercise and Lipoproteins in Postmenopausal Women

Abstract: The specific aims of this study were to quantify the effects of 12 weeks of resistance training, as well as a single session of resistance exercise on lipids and lipoproteins in obese, postmenopausal women. Twenty-one obese, postmenopausal women, not on hormone replacement therapy (age = 65.9 ± 0.5 yr; BMI = 32.7 ± 0.8 kg/m2), were randomly assigned to control (n=12) and exercise (n=9) groups matched for age and BMI. For 12 weeks, 3 days/week, the exercise group performed 10 whole body resistance exercises (3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 39 publications
5
21
0
8
Order By: Relevance
“…In one of the first studies in this field, Fahlman et al (2002) conducted a high intensity RT program three times a week for 10 weeks in older women and found significant improvements in the blood lipid profile and several studies have since replicated such findings (Fahlman et al, 2002;Ogawa et al, 2010;Wooten et al, 2011). In the present study no changes in blood lipids levels were found after either RT or MCT.…”
Section: Discussionsupporting
confidence: 59%
“…In one of the first studies in this field, Fahlman et al (2002) conducted a high intensity RT program three times a week for 10 weeks in older women and found significant improvements in the blood lipid profile and several studies have since replicated such findings (Fahlman et al, 2002;Ogawa et al, 2010;Wooten et al, 2011). In the present study no changes in blood lipids levels were found after either RT or MCT.…”
Section: Discussionsupporting
confidence: 59%
“…Wooten et al 37 verificaram os efeitos de 12 semanas de treinamento resistido (3 séries de 8 RM, três vezes/semanais, 10 exercícios para os grandes agrupamentos musculares) na composição corporal e perfil lipídico de mulheres obesas na pós-menopausa e observaram redução estatisticamente significante no colesterol total, LDL-c e não HDL-c em relação ao grupos controle não exercitado após o período de treinamento, no entanto, não houve diferença significante no peso corporal, IMC e composição corporal. Libardi et al 38 compararam os efeitos de 16 semanas de treinamento resistido (9 exercícios, 3 séries de 8-10 repetições máximas e 60-90 segundos de intervalo entre as séries) no perfil lipídico de mulheres de meia idade na pós-menopausa e concluíram que o colesterol total (-21.08%) e LDL (-38.53%) reduziram significativamente, no entanto, não houve diferença na fração HDL-c, triacilglicerol, peso corporal e IMC, demostrando que em mulheres na pós-menopausa o treinamento resistido de maneira sistematizada pode contribuir para redução do fatores de risco cardiovascular.…”
Section: Treinamento Resistidounclassified
“…Epidemiologic studies, clinical trials and current scientific literature show that increasing PL is directly linked to the progression of atherosclerotic plaques, either through deposition of lipoprotein debris on the arterial surface or in an indirect manner with predominance of lipoproteins such as chylomicrons, VLDL and LDL-c. 18 Postprandial lipemia is characterized by a state of hypertriglyceridemic transition and reflects an integrated measure of individual ability to remove TAG, the fasting concentrations of which, in turn, have been shown to be related to the size of LDL-c particles. This response can be subject to increased fatty acid mobilization, synthesis of VLDL-c and delays in its removal, providing greater interaction between lipoproteins and contributing to the formation of small dense particles of LDL-c, which are highly atherogenic.…”
Section: ■ Postprandial Lipemia As a Risk Factor For Development Of Cvdmentioning
confidence: 99%